Perubahan Gaya Hidup Pengguna e-commerce dalam Daya Beli Dikalangan Mahasiswa (Studi Kasus Mahasiswa Manajemen, Universitas Islam Negeri Sumatera Utara) - Zerimah Afgani Hasibuan; Nurbaiti Nurbaiti (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
E-commerce is inseparable from students. They generally always want to live an up to date and consumptive lifestyle, and for that fulfillment, they spend a lot of time with their gadgets to see what items are the latest and available on online shopping sites. the purpose of this research is to find out how the lifestyle changes of e-commerce users in purchasing power among students (Case Study of Management Students, State Islamic University of North Sumatra). This study uses descriptive qualitative research to describe the phenomenon, data, and previous research before drawing conclusions from the current difficulties. The results of the study, E-commerce has also changed the lifestyle of students, which can be seen from consumptive behavior. Consumptive lifestyle in students in terms of appearance and how to get along. Students who have a consumptive lifestyle always look attractive, wear branded fashion, keep up with the times quickly, and have a middle to upper standard of living. In addition, they associate more with people who have the same hobbies.